2013
DOI: 10.1590/s1516-14392013005000127
|View full text |Cite
|
Sign up to set email alerts
|

Some physical and mechanical properties of medium-density fiberboard made from giant bamboo

Abstract: The objective of this study was to evaluate the density, density profile, water swelling and absorption, modulus of elasticity and rupture from static bending, and tensile strength of experimental medium-density fiberboards manufactured using Dendrocalamus giganteus (Munro bamboo). The fiber production was carried out through the chemo-thermo-mechanical pulping process with four different conditions. The panels were made with 10% urea formaldehyde resin based on dry weight of the fibers, 2.5% of a catalyzer (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 5 publications
2
5
0
2
Order By: Relevance
“…Therefore, it is possible to observe that the panels with the highest proportions of P. edulis (T1 and T2) did not reach a minimum difference of 20%, while the other treatments remained within the range of 20% to 35%. This phenomenon was similar to the study conducted by MARINHO et al (2013), on bamboo Dendrocalamus giganteus fiberboards, with a maximum and minimum density gradient greater than 20%.…”
Section: Treatmentsupporting
confidence: 89%
“…Therefore, it is possible to observe that the panels with the highest proportions of P. edulis (T1 and T2) did not reach a minimum difference of 20%, while the other treatments remained within the range of 20% to 35%. This phenomenon was similar to the study conducted by MARINHO et al (2013), on bamboo Dendrocalamus giganteus fiberboards, with a maximum and minimum density gradient greater than 20%.…”
Section: Treatmentsupporting
confidence: 89%
“…FF-PAPI is foam, but epoxy composite is Solid core material. Compared with the flexural strength values of composites reinforced by kenaf bast fibers (28.4 MPa) and giant bamboo (9-11 MPa), which is reported by Ali et al [35] and Marinho et al [38], respectively. FF-PAPI/PR shows better properties than giant bamboo composites and similar properties to kenaf bast fibers composites.…”
Section: Mechanical Property Analysismentioning
confidence: 63%
“…The use of bagasse fibers in MDF panels showed that some properties exceeded the EN standards, except the thickness swelling values which were higher than requirements (Ashori et al, 2009). Physical and mechanical properties for MDF manufactured applying other types of wood and resins are also assessed in the works of Da Silva et al 2013and Marinhoa et al (2013) respectively, and important findings are established. There were other studies (Bektas et al, 2005;Taghiyari et al, 2016;etc), which were very relevant to the analysis of properties, either of particleboards or fiberboards made using specific and wood or under other effects, and good results in line with standards were established.…”
Section: Literature Reviewmentioning
confidence: 99%